Melatonin reverses urinary system and aorta damage in the rat due to chronic nicotine administration - ŞENER, GÖKSEL; ELÇİOĞLU, HATİCE KÜBRA (ROYAL PHARMACEUTICAL SOC GREAT BRITAIN, 2004)
We have evaluated the changes in contractile activity and oxidant damage of corpus cavernosum, urinary bladder, kidney and aorta after chronic nicotine administration in rats. The effects of melatonin on these parameters were investigated also. Male Wistar albino rats were injected intraperitoneally with nicotine hydrogen bitartrate (0.6 mg kg(-1) daily for 21 days) or saline. Melatonin (10 mg kg(-1), i.p.) was administered either alone or with nicotine injections. Corpus cavernosum, bladder and aorta were used for contractility studies, or stored with kidneys for the measurement of malondialdehyde and glutathione levels. Corpus cavernosum, bladder, and aorta samples were examined histologically and the extent of microscopic tissue damage was scored. In the nicotine-treated group, the contraction of corpus cavernosum, bladder and aorta samples and the relaxation of corporeal and aorta tissues decreased significantly compared with controls. However, melatonin treatment restored these responses. In the nicotine-treated group, there was a significant increase in the malondialdehyde levels of the corporeal tissue, bladder, kidney and aorta, with marked reductions in glutathione levels compared with controls. Melatonin treatment reversed these effects also. Melatonin administration to nicotine-treated animals caused a marked reduction in the microscopic damage of the tissues compared with those of the untreated group. In this study, nicotine-induced dysfunction of the corpus cavernosum, bladder and aorta of rats was reversed by melatonin treatment. Moreover, melatonin, as an antioxidant, abolished elevation in lipid peroxidation products, and reduction in the endogenous antioxidant glutathione, and protected the tissues from severe damage due to nicotine exposure.
Keywords: DEPENDENT ARTERIOLAR DILATATION; SUPEROXIDE-DISMUTASE; LIPID-PEROXIDATION; NITRIC-OXIDE; ENDOTHELIUM; REPERFUSION; ISCHEMIA; SMOKING